From Influence to Intention: How Peer Dynamics and Viral Marketing Shape Gen-Z Food Purchasing Through Brand Awareness - Ni Putu Olla Anggraeni; Ida Nyoman Basmantra (Jurnal Ekonomi Kreatif dan Manajemen Bisnis Digital, 2025)
Digital platforms and peer interactions play an increasingly central role in shaping Generation Z’s consumption behavior, yet limited empirical evidence clearly explains the distinct effects of peer influence and viral marketing on purchase intention through the mediating role of brand awareness, particularly in Bali’s food industry. This gap constrains marketers’ understanding of which social and digital factors are most influential at different stages of Generation Z’s purchasing process. Focused on Generation Z in Bali, this study explores the roles of peer influence and viral marketing in shaping food purchase intention, with brand awareness as a mediator. Employing a quantitative survey design, the data analysis indicates that viral marketing elevates brand awareness, which subsequently enhances purchase intention. Peer influence, however, exerts a direct effect on purchase intention but does not significantly impact brand awareness. The relationship between viral marketing and purchase intention is fully mediated by brand awareness. These findings highlight the distinct pathways through which digital content (viral marketing) and social interactions (peer influence) operate: the former builds brand recognition, while the latter directly drives purchase decisions. This study offers practical implications for food marketers by highlighting the importance of viral strategies that boost brand awareness, alongside using peer influence to convert awareness into purchase intention. Understanding Generation Z’s digital behavior and social interactions is essential for developing effective marketing strategies in today’s digital environment.